The broad spectral energy distributions of accreting white dwarfs - Lancaster, Tamara (Department of Astronomy, 2023)
Cataclysmic Variable stars (CVs) are excellent examples of multi-wavelength objects. They have been detected at all frequencies, from radio to γ-ray. However, while large sets of multi-wavelength data exist, few studies have been performed on the broad spectral energy distributions (SEDs) of these objects. I perform such a study here, and present the largest collection of broad CV SEDs yet constructed. I define a sample of well-studied, nearby cataclysmic variables of several different CV classes, and gather existing multi-wavelength data over a broad frequency domain. I identify the contributions to the spectrum and compare the spectra between classes. I then use the SEDs to constrain the mass accretion rates by modelling the accretion disc as a series of concentric annuli, each of which radiates as a black body with effective temperature appropriate to the radius of that annulus. The resulting bestfit accretion rates are compared to published values of mass accretion rates for the systems. My method of modelling the emission from a CV accretion disc as a sum of blackbodies produces accretion rate estimates that are reliable to within a factor of 5 for those systems that have steady state discs. However, the data are significantly underfitted by these simple models in all cases. While this method is a useful tool for modelling spectra and finding accretion rates, it cannot be applied to a small amount of data quickly and simply. It must be performed on as large a dataset as possible, and other contributions to the spectrum must be accounted for. As a result, an attempt to obtain accretion rate estimates for a larger, volume-limited sample of non-magnetic CVs was unsuccessful. I also investigate the ratios of flux densities in different wavebands. My data reveal two previously reported correlations, namely that shorter period CVs have higher X-ray to optical flux ratios and that magnetic CVs are X-ray bright compared to non-magnetic CVs. In addition, I find that polars are radio bright compared to IPs and non-magnetic CVs, and illustrate this, for the first time.